Business incubation program to create technopreneurs in the KOPMA UPI Cibiru - Hendriyana Hendriyana; Mochmad Iqbal Ardimansyah; Raditya Muhamad; Acep Supriadi (Universitas Muhammadiyah Magelang, 2022)
According to the Central Statistics Agency (BPS), the proportion of entrepreneurs in Indonesia was 3.1& of the total population in 2018. Although this ratio has improved over the previous year, it continues to lag behind neighboring countries. To increase the ratio of entrepreneurship, interest must be promoted at a young age, and one way to do so is to introduce entrepreneurship through the use of technology, or technopreneurs, in an university environment, which plays an important role in the creation of creative and innovative talents. The objective of this program is to introduce students to technopreneurs via a business incubation program. Coaching and mentoring are the methods used in this business incubation program. The instruments used to evaluate the business incubation program are (1) understanding of the material, (2) motivation to apply the material to the business model, and (3) implementation of the business incubation program. The evaluation revealed that 98.04% of participants thought the business incubation program activities were beneficial and they were interested in applying the material to their current or future businesses.